The relationship between price and financial stability in new monetary policy designs: the case of the US using the TVP-SVAR model - Çelik, Ali Kemal; Yalçinkaya, Ömer; Emsen, Hatira Sadeghzadeh (Estudios de Economía, 2021)
This study aims to explain the relationship between price and financial stability in monetary policy designs that have developed since the 1990s and to empirically examine the relationship between price and financial stability in the monetary policy designs of the US. To this effect, the study examines the time-varying structure of the relationship between price and financial stability in the US, where monetary policies are designed to achieve price stability, full employment and moderate long-term interest rate targets using the TVP-SVAR model for the period 1993:12-2020:12. The results of the study demonstrate the presence of a reciprocal relationship within the scope of the new environment hypothesis, which varies over time between price and financial stability in the US over the study period. These results broadly suggest the necessity of redesigning monetary policies in the US based on the propositions of the new environment hypothesis and considering the varying structure of the relationships, symmetrical or asymmetrical, between monetary and financial stability variables over time.